2010
DOI: 10.1155/2010/457236
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Rothia mucilaginosa DY-18: A Clinical Isolate with Dense Meshwork-Like Structures from a Persistent Apical Periodontitis Lesion

Abstract: Rothia mucilaginosa is an opportunistic pathogen in the human oral cavity and pharynx. We found that R. mucilaginosa DY-18, a clinical isolate from a persistent apical periodontitis lesion, had biofilm-like structures. Similar structures were also observed on R. mucilaginosa ATCC25296. To further study these structures, we determined the complete genome sequence of DY-18 and found it a 2.26-Mb chromosome. Regarding stress responsive systems known to affect biofilm formation in many bacteria, DY-18 genome posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…also associated with the skin, and Enterococcus faecalis is also found in the gastrointestinal tract (14,(40)(41)(42)(43)(44)(45). These viability data paired with our FISH probe results demonstrated that biofilms within carotid arterial plaque lesions contained viable bacteria that were, at least in some cases, polymicrobial infections.…”
Section: Discussionsupporting
confidence: 76%
“…also associated with the skin, and Enterococcus faecalis is also found in the gastrointestinal tract (14,(40)(41)(42)(43)(44)(45). These viability data paired with our FISH probe results demonstrated that biofilms within carotid arterial plaque lesions contained viable bacteria that were, at least in some cases, polymicrobial infections.…”
Section: Discussionsupporting
confidence: 76%
“…Rothia species are components of the oral microbiota and were also identified in duodenal biopsy specimens (67). Although some infections by R. mucilaginosa have been described, this species is considered a harmless colonizer of the oral cavity (68). Recently, it was hypothesized that some species of the Rothia genus, including R. mucilaginosa, are involved in gluten degradation (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…(v) An intact, toxin-producing strain of C. diphtheriae has 11 more pathogenicity islands and 37 additional regions, compared with C7(ÏȘ), a nontoxigenic strain of that species (26). Among medically relevant coryneforms, stress-responsive systems that regulated the biofilm phenotype have been characterized from a mucoid strain of Rothia mucilaginosa (54).…”
mentioning
confidence: 99%